Critical Decision Method Interviews to Understand the Initial Treatment Planning Process in Foster Care. (September 2022) - Wurst, Connor; Winnie Chen, Huei-Yen; Sage, Melanie; Joseph, Kenneth; Maggiulli, Laura
In foster care settings, the treatment plan captures goals and interventions for youth in care. The first version of this plan is typically due 30 days after the youth is enrolled in the foster care program, leading to a challenging month of assessing the case and developing the treatment plan. This study utilized Critical Decision Method interviews with care coordinators and clinicians to understand the decision-making involved in balancing assessment tasks, and the barriers to using assessment to inform treatment. The interviews were coded to identify major themes including information sources and constraints. These identified themes and general understanding of the problem space will drive future work developing interventions to improve the workflow process and drive better outcomes for youth in foster care.